Enhancement of the Pitting Corrosion Resistance of AISI 316LVM Steel with Ta-Hf-C/Au Bilayers for Biomedical Applications. (17th January 2017) - Guzmán, Pablo; Aperador, Willian; Yate, Luis
Abstract : Tantalum carbide (TaC), hafnium carbide (HfC), and Ta-Hf-C mixed coatings with and without a gold (Au) interlayer were deposited on 316LVM steel substrates by the magnetron cosputtering technique in order to improve the corrosion resistance of steel substrates in a simulated biological fluid. To study the effect of the gold interlayer on pitting corrosion, the different systems were placed in contact with Ringer's solution at pH 7.4 and a temperature of 37°C. The electrochemical properties of the coatings were determined using polarization curves. Subsequently, the surface morphologies were observed using scanning electron microscopy (SEM) in order to analyze the corrosion processes on the different surfaces. The gold interlayer was found to significantly improve the electrochemical properties of the system, showing a decrease in the pitting corrosion and deterioration rate, while it is expected that the binary and ternary carbides provide mechanical stability to the bilayers protecting the gold.